AHAMKARA AND FORGIVENESS: THE MEDIATING ROLE OF ANASAKTI - Samiksha (My University, 2026)
A vital psychological construct that is important for psychological adjustment, healthy interpersonal relations, and emotional wellness is forgiveness. Exploring the relationship between Ahamkara, Anasakti, and Forgiveness, as well as the mediating role played by Anasakti in the relationship between Ahamkara and Forgiveness was the main objective of the present study. Anasakti refers to non-attachment, emotional stability, and lack of preoccupation with outcomes in Indian psychology, whereas Ahamkara refers to the ego and self-identity. Acquiring knowledge about these concepts would assist one in comprehending the psychological process of forgiveness better. 151 individuals (85 women and 66 men), who ranged in age from 18 years to 40 years, participated in the online survey. The measures used in the study included Heartland Forgiveness Scale, Anasakti Scale, and the Aham Inventory. Multiple regression, mediation analysis, and Pearson correlation were used to test the hypothesized relationships. The higher scores of Ahamkara were associated with higher scores of forgiveness as per the findings of the study, which revealed that there was a significant positive correlation between both factors. However, there was no apparent relationship found between Anasakti and forgiveness and between Anasakti and overall Ahamkara. There were some important relationships found between Ahamkara, Anasakti, and Forgiveness at the subscale level. Mediation analysis did not reveal that Anasakti had a significant mediating role between overall Ahamkara and forgiveness. But the relationship between Identification and Forgiveness of Situations was mediated by Outcome Vulnerability. The findings show the diverse nature of Ahamkara and Anasakti and suggest that the effect of these two constructs on forgiveness operates through specific dimensions and not through general constructions. With empirical support for the importance of indigenous concepts in understanding the phenomenon of forgiveness, the research makes a contribution to the growing body of literature on Indian psychology.
Keywords: Ahamkara; Anasakti; non- attachment; forgiveness; Indian psychology